2020
DOI: 10.17109/azh.66.suppl.169.2020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different habitat parameters on carabid beetle assemblages in selected areas of a forest-field landscape in Poland – 10 years of data

Abstract: Long-term data on carabid beetles assemblages on differently managed study sites in forests and open areas were analysed to study the impact of selected environmental factors on the carabid assemblages of both the individual study sites over the years and the set of all study sites in selected years.Ordination separated forest stands from open areas along with the first, and samples of 2011 from those of 2015 along the second axis. For study sites in forest stands in most cases, precipitation was a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…We could also show differences in the most important factors between the groups (hypothesis (3)). The formation of characteristic assemblages in these two taxonomic groups for the study sites in the research area has been shown in former studies, e.g., Szyszko-Podgórska [33]; Schwerk et al [70]. The sensitive reaction of carabid beetles to soil pH has also been previously reported, e.g., Koivula [25]; Zumstein et al [71]; Nietupski et al [72].…”
Section: Carabids and Butterfliessupporting
confidence: 62%
“…We could also show differences in the most important factors between the groups (hypothesis (3)). The formation of characteristic assemblages in these two taxonomic groups for the study sites in the research area has been shown in former studies, e.g., Szyszko-Podgórska [33]; Schwerk et al [70]. The sensitive reaction of carabid beetles to soil pH has also been previously reported, e.g., Koivula [25]; Zumstein et al [71]; Nietupski et al [72].…”
Section: Carabids and Butterfliessupporting
confidence: 62%
“…In the second year, LAI remained a signi cant factor, but some other factors were also signi cant, namely high soil temperature (in areas between tree crowns on the ground) and soil carbon content (for carabids living in the least disturbed stands and under tree crowns). Higher C content in the organic soil layer is conducive to forest assemblages of carabids (Schwerk et al 2020), because it is associated with greater species diversity of litter and soil micro-and macrofauna, which results in better trophic conditions for forest species of ground beetles associated with forest litter.…”
Section: Ground Beetles and Environmental Variablesmentioning
confidence: 99%